Role of impaired iron transport on exercise performance in heart failure patients. (3rd October 2022) - Lo Russo, G; Agostoni, P G; Campodonico, J; Junod, D; Carulli, E; Gaudenzi Asinelli, M; Doni, F; Bonomi, A
Abstract: Aims: Impaired iron transport (IIT) occurs frequently in heart failure (HF) patients, even in the absence of anaemia and it is associated with a poor quality of life and prognosis. The impact of IIT on exercise capacity, as assessed by the cardiopulmonary exercise test (CPET), in HF is at present unknown. The aim of this article is to evaluate in HF patients the impact on exercise performance of IIT, defined as transferrin saturation (TSAT) <20%. Methods and results: We collected data of 676 patients hospitalised for HF. All underwent laboratory analysis, cardiac ultrasound, and CPET. Patients were grouped by the presence/absence of IIT and anaemia (haemoglobin <13 and <12 g/dL in male and female, respectively): Group 1 (G1) no anaemia, no IIT; Group 2 (G2) anaemia, no IIT; Group 3 (G3) no anaemia, IIT; Group 4 (G4) anaemia and IIT. Peak oxygen uptake (peakVO2) reduced from G1 to G3 and from G2 to G4 (G1: 1266±497 mL/min, G2: 1011±385 mL/min, G3: 1041±395 mL/min, G4: 833±241 mL/min), whereas the ventilation to carbon dioxide relationship slope (VE/VCO2 slope) increased (G1: 31.8±7.5, G2: 34.5±7.4, G3: 36.1±10.2, G4: 37.5±8.4). At multivariate regression analysis, peakVO2 independent predictors were anaemia, brain natriuretic peptide (BNP), and left ventricular ejection fraction, whereas VE/VCO2 slope independent predictors were IIT and BNP. Conclusions: In HF IIT is associated with exercise performance impairment independently from anaemia, and it is a predictor of elevated VE/VCO2 slope, a pivotal index of HF prognosis. Funding Acknowledgement: Type of funding sources: Private hospital(s). Main funding source(s): Centro cardiologico Monzino, Italy